The Impact of Business Risks on the Quality of the Audit Process - Rieka Ramadhaniyah; Anik Irawati; Nolita Yeni Siregar; Reva Meiliana (Proceeding International Conference on Information Technology and Business, 2020)
The purpose of this study was to explain the effect of business risk on the quality of the auditing process from the perspective of auditors. The collecting data used a questionnaire distributed to several auditors in the public accounting firm. The population in this study was external auditors who worked in several public accounting firms with the sample selection using purposive sampling. The questionnaires distributed were as many as questionnaires, but there were only 42 returned questionnaires. The analysis technique used multiple linear regression. The result of this study showed that systematic risk was proxied by the litigation ratio which affected the quality of the audit process, the effect of environmental risk was proxied by the sanctions received by KAP affected the quality of the audit process. Furthermore, work risk was proxied by audit risk on the quality of the audit process.Keyword: Business Risk, Quality Audit Process